2020
DOI: 10.1029/2019jd031304
|View full text |Cite
|
Sign up to set email alerts
|

Data Assimilation for Climate Research: Model Parameter Estimation of Large‐Scale Condensation Scheme

Abstract: This study proposes using data assimilation (DA) for climate research as a tool for optimizing model parameters objectively. Mitigating radiation bias is very important for climate change assessments with general circulation models. With the Nonhydrostatic ICosahedral Atmospheric Model (NICAM), this study estimated an autoconversion parameter in a large-scale condensation scheme. We investigated two approaches to reducing radiation bias: examining useful satellite observations for parameter estimation and expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The LETKF has been used in operational NWP systems by the Deutscher Wetterdienst (DWD) and the Japan Meteorological Agency (JMA). In addition, recent studies have shown that the LETKF can be used to optimize tuneable parameters of NWP models (Ruiz et al ., 2013; Ruiz and Pulido, 2015; Kotsuki et al ., 2018, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The LETKF has been used in operational NWP systems by the Deutscher Wetterdienst (DWD) and the Japan Meteorological Agency (JMA). In addition, recent studies have shown that the LETKF can be used to optimize tuneable parameters of NWP models (Ruiz et al ., 2013; Ruiz and Pulido, 2015; Kotsuki et al ., 2018, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For the SCALE-RM, it would be beneficial to optimize a microphysics parameter such as a coefficient for terminal velocity using the state augmentation method (Aksoy et al, 2006;Kotsuki et al, 2018Kotsuki et al, , 2020 and to use a multi-moment microphysics scheme (e.g., Seiki & Nakajima, 2014) to model clouds and cold pools more reasonably (Dawson et al, 2010). The use of a multi-moment microphysics scheme requires tuning of the observation operator but would enable us to effectively use polarimetric information from the MP-PAWR observations (Putnam et al, 2019;Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cloud and precipitation parameter estimation has been tried in simpler contexts (e.g. Norris and Da Silva, 2007;Posselt and Vukicevic, 2010;Posselt and Bishop, 2012) and within more complete atmospheric models (Ollinaho et al, 2013;Posselt, 2016;Ruckstuhl and Janjić, 2020;Kotsuki et al, 2020). However it has not yet reached a level of development to have been used in operational weather forecasts.…”
Section: Parameter Estimation Methodologymentioning
confidence: 99%
“…The process of learning model parameters using data assimilation is known as parameter estimation, with cloud and precipitation parameters a major target (e.g. Norris and Da Silva, 2007;Ruckstuhl and Janjić, 2020;Kotsuki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%